Notes for reflection on the professional character of schools for social hygiene visitors (Papeles, 2023)
The following work is part of my doctoral thesis in process about "The professional intervention of the agents of the Social Service in the city of La Plata 1930-1955" in which I intend to carry out an investigation about the process of professionalization of assistance social in the city of La Plata.The objective of this work is to present the contributions of the sociology of professions and historical studies about the development of professions in Argentina in order to review which theoretical conceptions can be useful for the historical study of the first experiences of academic training of the social service agents, who in the case of the city of La Plata were Social Workers. For this, the work is structured in three moments: in principle I will review how the professional character was thought from the studies carried out by the discipline itself, then the contributions of sociology and history about how to think about these knowledge and professions, and finally Potential dialogues with these contributions will be presented to think about the professional historical character of the hygiene visit
Keywords: Profession; Sociology of Professions; Social Workers; History; Social Work